Explaining the cross-section of asset returns with Google Trends - Saarenpää, Elmeri (My University, 2021)
This thesis explains the cross-section of stock asset returns with Google Trends using methods from multiple studies. Risk factors set asset prices and explain differences in average returns. The five-factor model (FF5) of Fama and French (2015) can explain most of the expected stock returns. However, research on alternative factors may identify new risk premiums. Market sentiment combines behavioral finance with asset pricing. One approach quantifies sentiment from internet searches using Google Trends search volume indices. However, the methods of the previous studies may not apply to asset pricing. In this study, I construct synthetic sentiment indices based on the Google Trends data consisting of the 98 search terms Preis, Moat, and Stanley (2013) propose. I use principal component analysis, suggested by Baker and Wurgler (2006), to construct the sentiment indices. Then, I explain the returns of both Fama–French portfolios and individual stocks with the sentiment indices. The models used in testing also contain the FF5 factors and self-constructed cross-sectional factors. Hypothesis testing includes various regression methods, such as the procedure of Fama and MacBeth (1973). The monthly data ranges from the year 2004 to 2017 and is limited to the United States. The synthetic sentiment indices constructed in this thesis do not relate to aggregate stock market movements. Based on the t-statistics of regressions, the sentiment factors are not significant when applying appropriate clustering and standard error corrections methods. Also, the Google Trends-based sentiment does not explain the cross-section of asset returns. The t-statistics of the Fama–MacBeth regressions do not indicate any compensation from the exposure to the Google Trends-based sentiment factors. The risk premiums are not significant even at a 90% confidence level. Based on the literature, new factors and approaches may strengthen the understanding of the expected asset returns. The availability and the amount of Google Trends data make it an appealing source for sentiment proxies. However, it may not be as beneficial of a tool as previous studies indicate. Different search term specifications, periods, and data frequencies offer an opportunity for further research.

Tämä tutkielma selittää arvopaperien tuottojen poikkileikkausta Google Trends -datan avulla käyttäen eri tutkimusten menetelmiä. Riskifaktorit määrittävät arvopaperien hinnat ja selittävät keskimääräisiä tuottoeroja. Faman ja Frenchin (2015) viiden faktorin malli (FF5) selittää suurimman osan odotetuista osaketuotoista. Vaihtoehtoisten faktoreiden tutkimus saattaa kuitenkin tunnistaa uusia riskipreemioita. Markkinasentimentti yhdistää käyttäytymistieteellisen rahoituksen arvopaperien hinnoittelun. Yksi lähestymistapa mittaa sentimenttiä Google Trends -palvelun hakuvolyymi-indeksien avulla. Aiempien tutkimusten menetelmät saattavat kuitenkin olla soveltumattomia arvopapereiden hinnoitteluun. Tässä tutkimuksessa Google Trends -dataan pohjautuvat synteettiset sentimentti-indeksit perustuvat 98 Preisin, Moatin and Stanleyn (2013) ehdottamaan hakusanaan. Sentimentti-indeksit muodostetaan käyttämällä pääkomponenttianalyysia, kuten Baker ja Wurgler (2016) suosittelevat. Sekä Fama–French-portfolioiden että yksittäisten osakkeiden tuottoja selitetään näiden sentimentti-indeksien avulla. Testauksessa käytettävät hinnoittelumallit sisältävät myös FF5-faktorit ja itse luodut poikkileikkausfaktorit. Hypoteesin testaukseen sovelletaan useita regressiomenetelmiä, kuten Faman ja MacBethin (1973) menetelmää. Kuukausidata vuosilta 2004–2017 on rajattu Yhdysvaltoihin. Tässä tutkielmassa luoduilla synteettisillä sentimentti-indekseillä ei ole yhteyttä osaketuottoihin kokonaisuudessaan. Regressiotulosten t-arvojen mukaan sentimentti ei ole merkitsevä asiaankuuluvan klusteroinnin ja keskivirheiden korjauksen jälkeen. Google Trends -dataan pohjautuva sentimentti ei myöskään selitä arvopapereiden tuottojen poikkileikkausta. Fama–MacBeth-regressioiden t-arvot osoittavat, ettei altistumisesta sentimentti-indekseille palkita. Riskipreemiot eivät ole merkitseviä edes 90 % luottamustasolla. Kirjallisuus esittää uusien faktoreiden ja menetelmien voivan vahvistaa käsitystä arvopapereiden odotetuista tuotoista. Google Trends -datan saatavuus ja laajuus tekevät siitä houkuttelevan lähteen sentimenttianalyysiin, mutta tämän hyödynnettävyys saattaa olla uskottua heikompi. Erilaiset hakutermiyhdistelmät, aikaperiodit ja datafrekvenssin muuttaminen tarjoavat jatkotutkimusmahdollisuuksia.
Keywords: asset pricing, risk premium, market sentiment, big data, principal component